Glycolipids chemical informatics - Hashim, Rauzah; Janarthanan, Sri Ganesh (Malaysian Journal of Science, 2001)
Information on new chemicals and biologically active compounds increase tremendously through the lntemet database. Our current project is to build a comprehensive database on Malaysian Natural Product that has vast potentials in medicinal and commercials values. Building a database means development of all the necessary entities to define suitable properties for the Natural Product database. We have used and object-oriented database engine for this information system. From this system we shall also develop a glycolipid chemical information system. Glycolipid forms a class of carbohydrate liquid crystals, commonly found in nature and living cells. Many can be also be synthesized chemically and enzymatically. Their liquid crystalline behavior is mostly unknown; hence their potential as specialty fine chemicals is under exploited. The study of liquid crystal properties of glycolipid is essential both fundamentally and more importantly for their applications.